Effects of endothelin-1 1-31 on cell viabililty and [Ca2+]i in cultured neonatal rat cardiomyocytes - Ren, A. J; Yuan, X; Lin, L; Pan, Y. X; Qing, Y. W; Yuan, W. J (Physiological research, 2008)
We previously found that endothelin-1(1-31) (ET-1(1-31)) exhibited a pro-arrhythmogenic effect in isolated rat hearts. In this study, we further investigated the effects of ET-1(1-31) on a cell viability and observed [Ca(2+)](i) in cultured cardiomyocytes. Cultured neonatal rat cardiomyocytes were treated with 0.1, 1, and 10 nM ET-1(1-31) for 24h in the presence or absence of ET(A) receptor antagonist (BQ(123)) or phosphoramidon, a NEP/ECE inhibitor. Cell injury was evaluated by supernatant lactate dehydrogenase (LDH) assay, superoxide dismutase (SOD) activity, and malondialdehyde (MDA) content. Cell viability was assessed by MTT assay. [Ca(2+)](i) was measured with Fluo-3/AM under a laser confocal microscope. 1) ET-1(1-31) dose-dependently increased LDH release and decreased cell viability. 2) LDH and MDA levels were significantly elevated and SOD activity decreased after administration of 1 nM ET-1(1-31) for 24h, and these changes were markedly attenuated by 1 uM BQ(123). 3) Exposure to 10 nM ET 1(1-31) caused a continuous increase in [Ca(2+)](i) to cultured beating cardiomyocytes and termination of [Ca(2+)](i) transient within 6 min, and this change was reversed by 1 uM BQ(123) and attenuated by 0.5 mM phosphoramidon. These results suggest that ET-1(1-31) could cause cell injury, and that the effect of ET-1(1-31) on [Ca(2+)](i) transients is mainly mediated by ET(A) receptor and partially attributed to the conversion of ET-1(1-31) to ET-1(1-21).
Keywords: Endothelin-1; Cell Survival; Glycopeptides; Malondialdehyde; Microscopy, Confocal; Metalloendopeptidases; inhibitory proteas; kardiomyocyty; metaloendopeptidasy; Dose-Response Relationship, Drug; receptor endotelinu A; novorozená zvířata; Superoxide Dismutase; financování organizované; endotelin-1; konfokální mikroskopie; krysa rodu Rattus; Time Factors; superoxiddismutasa; Financing, Organized; zvířata; Calcium Signaling; Cells, Cultured; Myocytes, Cardiac; časové faktory; cyklické peptidy; Animals, Newborn; Peptide Fragments; antagonisté endotelinového receptoru A; potkani Sprague-Dawley; L-Lactate Dehydrogenase; Peptides, Cyclic; Receptor, Endothelin A; kultivované buňky; vápníková signalizace; peptidové fragmenty; Rats; vztah mezi dávkou a účinkem léčiva; Rats, Sprague-Dawley; Animals; Endothelin A Receptor Antagonists; L-laktátdehydrogenasa; aspartátové endopeptidasy; Aspartic Acid Endopeptidases; malondialdehyd; Protease Inhibitors; viabilita buněk; glykopeptidy